Time-Tangent Surfaces Around Biharmonic Particles and Its Lorentz Transformations in Heisenberg Spacetime - Korpinar, Talat; Turhan, Essin (Springer/Plenum Publishers, 2013)
In this work, we introduce a new spacetime using Heisenberg group and call this space as Heisenberg spacetime. We give a geometrical description of time-tangent surfaces around timelike biharmonic particle in . Moreover, we obtain Lorentz transformations this particles. Additionally, we illustrate our results in Figs. 1-6.
Keywords: Energy; Bienergy; Heisenberg group; Faraday tensor; Lorentz transformations